(untitled) (Upper Saddle River, N.J., 2001)
This comprehensive guide to programming in XML teaches readers how to use XML to create customized tags and addresses standard custom markup languages for science and technology, multimedia, commerce, and other fields. Includes a concise introduction to Java, as well as cutting edge topics such as XQL, SMIL and VoiceXML as well as a real-world e-Commerce case study. Also includes a complete chapter on Web-accessibility that addresses VoiceXML. Provides hundreds of valuable programming tips. For XML programmers and Internet/Web programmers.
Keywords: XML (Ngôn ngữ đánh dấu tài liệu),XML (Document markup language)